Pengaruh Kinerja Keuangan Terhadap Harga Saham: Studi Pada Perusahaan Consumer Goods Yang Terdaftar di Bursa Efek Indonesia 2021 – 2023 - Nur Billa Rahmawati; Agus Wahyudi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to analyze the influence of financial performance on stock prices. Economic performance is measured using liquidity, solvency, and profitability ratios. Current Ratio (CR) is used to measure liquidity ratios, Debt to Equity Ratio (DER) is used to measure solvency ratios, and Return on Equity (ROE) is used to measure profitability ratios. The research sample used consumer goods sector companies listed on the Indonesian Stock Exchange (BEI) for the 2021-2023 period, with the regression model used is multiple linear regression. The research results show that partially, the Current Ratio (CR) does not have a significant effect on stock prices. Meanwhile, Debt to Equity Ratio (DER) and Return on Equity (ROE) significantly influence stock prices. The ratios presented in financial reports provide sufficient information that investors need in making decisions. With relevant information from the financial reports presented by the company, investors can avoid mispricing which often occurs in share prices in the capital market.